Gastric mucosal damage with aspirin: results of experimental models in adult albino rats - Fayyaz, Asma; Samad, Afra; Waseem, Uzma; Shafique, Sadaf; Nasreen, Shagufta; Hussain, Sadia (International Journal Of Community Medicine And Public Health, 2020)
Background: Non-steroidal anti-inflammatory drugs are the over-the-counter available medicine and are notorious for their potential in causing peptic ulcer disease. Aspirin in used to treat cardiovascular disease and are commonly prescribed medicine. Methods: 24 healthy albino rats of either sex were purchased and kept at controlled in controlled environment. These are mainly divided into the two groups named as group A and group B having 12 rats in each group. 25 gm of the powdered henna was mixed in 250 ml distilled water. Aspirin was used in the dose of 100 mg/kg drug solution is prepared every day before administration. Animals were sacrificed from each group on day 8th and 15th. Macroscopic ulcer was identified and Fibroblast, inflammatory cells, congested blood vessels were counted. SPSS version 21 was used to statistically analyse the data. P value of ≤0.05 was considered as statistically significant. Results: aspirin group have more ulcer, congested blood vessels, inflammatory infiltrate and increased number of fibroblasts compared to control. The values were statistically significant with p value less than 0.05. Conclusions: gastric ulcer is quite common and it occur because of the imbalance between protecting and aggravating factors. aspirin is a common offender of gastric ulcer because of its common use.